Buffering Performance of High-Speed Impact Space Penetrator with Foam-Filled Thin-Walled Structure - Haitao Luo; Yuxin Li; Guangming Liu; Changshuai Yu; Shipeng Chen (Shock and Vibration)
High-speed penetrators carrying detection equipment impact planetary bodies at high speeds, and they are therefore buried at depths of up to several meters beneath the surface. During the friction and collision with the crust of the planet, the acceleration of the scientific instrumentation is significantly large. The vibration protection structure for scientific instrumentation is necessary for the reduction of the peak value of the acceleration response and the improvement of the survival rate. In this study, a penetrator with a multilayered energy absorbing structure was developed to improve the survival rate of the penetrator, of which the foam-filled thin-walled structure (FTS) was applied to the penetrating vibration-damping structure. The penetration process of the penetrator into the planetary medium was simulated using the LS-DYNA software platform. The results obtained using empirical formulas and theoretical derivations were compared with the results of the numerical analysis. The reliability of the penetrator limit element model was then verified by conducting an impulse response experiment and simulation. The results suggest that FTS has a positive influence on the isolation impact and energy absorption. Moreover, the vibration isolation effects of nine different FTSs were evaluated with respect to the following six factors: impact isolation efficiency, load efficiency, peak of acceleration, peak impact force, total energy absorption, and specific energy absorption. Furthermore, the design of the damping structure provides an indispensable solution for penetrator detection.